Politics of external debt and millennium development goals: a case study of Nigeria(2000-2015) - Moniruzzaman, Md.; Mikail, Shafiu Yahya (Medwell Journals, 2016)
Abstract: Foreign aid is considered as a significant source of income for many developing countries. Countries that were facing current account deficit in the 1950s were encouraged to borrow from international financial institutions to boost their economic growth. However, such borrowing created a great obstruction to the economic growth of many developing countries today due to high obligations on external debt. Like many developing countries, Nigeria has been living under horrific debt burden. Servicing this debt has cost the country an average of $2.0 billion annually. This, study aims to examine Nigeria’s external debt and its impact in realizing Millennium Development Goals (MDGs). The central argument of this study is that external debt has severely limited the ability of the government to devote recourses into the MDGs. The negative impact of external debt is measured by comparing the annual debt service with the ratio of government expenditure in eight MDGs, whereby it shows that Nigeria’s government has not been able to allocate sufficient resources towards the realization of MDGs due to its obligation to channel a substantial percentage of its GDP to meet external debt service.